Characterisation of Fourteen Accessions of Trichosanthes cucumerina from Nigeria Using Internal Transcribed Spacer - Ann Osuagwu; Celestine Uzoma Aguoru; Lucky Osabuohien Omoigui; Joseph Olalekan Olasan (Journal of Genetic Resources)
Snake gourd botanically known as Trichosantes cucumerina locally called tomato agwo. T.cucumerina is considered a neglected and underutilised crop. Detailed characterisation of this crop is not known in Nigeria and other African countries. This study was done to access fourteen accessions of T. cucumerina from Nigeria using Internal Transcribed Spacer (ITS). The fourteen accessions from different ecological regions were sequenced with ITS1 and ITS4 by direct PCR products. The results obtained were at minimum (570) and maximum (580) base pairs. The query coverage ranging from 99.4 % to 100 % affirms positive amplification and sequencing of snake gourd ecotypes using ITS1 and ITS4. The phylogenetic tree of the characterization group T. cucumerina was divided into three clusters. The phylogenetic tree of the characterization grouped T.cucumerina into three clusters. The genetic distances between the samples revealed that Ukwa, NACGRAB, Ikwuano, Oshogbo, Ikom, and Rumibekwe were closely related. Benin, Nasarawa, Oye-Ekiti, Ilorin, and NHST-0583 shared no genetic relationship as revealed by their genetic distances. The genetic distance ranged from 0.217 - 2.010. T. cucumerina landraces studied in Nigeria thirteen were T. cucumerina var anguina. The NHST -0583 from the seed center was the only T.cucumerina var cucumerina in Nigeria. This was blasted on the National Center for Biotechnology Information (NCBI) website. The sequenced blast in the NCBI data website was to be similar to accession numbers GU059528.1 and GQ240883.1 respectively. These have given scientists critical knowledge regarding T. cucumerina molecular breeding in Nigeria.